Fibroblast Activation Protein Overexpression and Clinical Implications in Solid Tumors: A Meta-Analysis - Liu, Fang; Qi, Li; Liu, Bao; Liu, Jie; Zhang, Hua; Che, DeHai; Cao, JingYan; Shen, Jing; Geng, JianXiong; Bi, Yi; Ye, LieGuang; Pan, Bo; et al. (PLOS ONE, 2015)
Objective Fibroblast activation protein (FAP) plays a vital role in tumor invasion and metastasis. Previous studies have reported its prognostic value in different tumors. However, the results of these reports remain controversial. In this study, a meta-analysis was performed to clarify this issue. Methods A search of the PubMed, Embase and CNKI databases was conducted to analyze relevant articles. The outcomes included the relations between FAP expression and histological differentiation, tumor invasion, lymph node metastasis, distant metastasis and overall survival (OS). Sensitivity analysis by FAP expression in different cells and tumor types were further subjected to sensitivity analyses as subgroups. Pooled odds ratios (ORs) and hazard ratios (HRs) were evaluated using the random-effects model. Results The global analysis included 15 studies concerning various solid tumors. For global analysis, FAP overexpression in tumor tissue displayed significant associations with poor OS and tumor progression (OS: HR = 2.18, P = 0.004; tumor invasion: OR = 4.48, P = 0.007; and lymph node metastasis: OR = 3.80, P = 0.004). The subgroup analyses yielded two notable results. First, the relation between FAP overexpression and poor OS and tumor lymph node metastasis was closer in the patients with FAP expression in tumor cells. Second, the pooled analyses of colorectal cancers or pancreatic cancers all indicated that FAP overexpression was associated with a detrimental OS (HR: 1.72, P = 0.009; HR: 3.18, P = 0.005, respectively). The magnitude of this effect was not statistically significant compared with that in patients with non-colorectal cancers or non-pancreatic cancers. These analyses did not display a statistically significant correlation between FAP expression and histological differentiation and distant metastasis in all of the groups. Conclusions FAP expression is associated with worse prognosis in solid tumors, and this association is particularly pronounced if FAP overexpression is found in the tumor cells rather than the stroma.